2005
DOI: 10.1088/0953-2048/18/5/022
|View full text |Cite
|
Sign up to set email alerts
|

The effect of nanoscale Fe doping on the superconducting properties of MgB2

Abstract: Iron is an important sheath material for fabrication of MgB 2 wires. However, the effect of Fe doping on the superconducting properties of MgB 2 remains controversial. In this work, we present results of nanoscale Fe particle doping in to MgB 2 . The Fe doping experiments were performed using both bulk and thin film form. It was found that Fe doping did not affect the lattice parameters of MgB 2 , as evidenced by the lack of change in the XRD peak positions for MgB 2 . Because of the high reactivity of nano-sc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
34
3
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 19 publications
2
34
3
2
Order By: Relevance
“…Not only the amount of added Mg turnings but the heating rate also controls the amount of Mg/MgO in the end product. In the present study instead of using Mg/MgO as pinning centers in MgB 2 , we added nano-Co 3 O 4 in the pristine We also compare our present results of nano-Co 3 O 4 doped MgB 2 with various other reports [3][4][5][6][7][8] on different nano-particle doped MgB 2 . We found that in most of the nano-particle doped MgB 2 , the high J c is coupled with low field and low temperature fluxiod jumps.…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…Not only the amount of added Mg turnings but the heating rate also controls the amount of Mg/MgO in the end product. In the present study instead of using Mg/MgO as pinning centers in MgB 2 , we added nano-Co 3 O 4 in the pristine We also compare our present results of nano-Co 3 O 4 doped MgB 2 with various other reports [3][4][5][6][7][8] on different nano-particle doped MgB 2 . We found that in most of the nano-particle doped MgB 2 , the high J c is coupled with low field and low temperature fluxiod jumps.…”
Section: Introductionmentioning
confidence: 70%
“…By now a number of articles had appeared on the critical current density of nano particle doped MgB 2 for example nano-SiO 2 [3], nano-Fe [4], nano-diamond [5], nano-SiC [6], nanoTiO 2 [7], nano-Al 2 O 3 [8] and others. Not only the doped nano-particles but various routes of synthesis had also resulted in improved critical current density of this compound [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Although most publications report enhancement of in-field J c and B irr [6,7,8,9] upon doping of MgB 2 with magnetic nanoparticles, the actual situation is not so clear. In particular, there are some observations of detrimental influence of magnetic nanoparticles on J c of MgB 2 [10,11] and also direct, transport J c measurements on MgB 2 wires doped with magnetic nanoparticles are still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…On contrary, either the sizes of the MgB2 crystallites in the resulting MgB2 sample (formed after the addition of the nanoparticles to Mg and B precursor powders and sintering at various temperatures) are given, [20] or they do not give any information about the sizes of the crystallites. [21,[23][24][25] The same stands for the MgB2 grain sizes determined from electron microscopy observation (mostly from SEM). This work gives an insight in how the addition of the NiCoB nanoparticles affects the sizes of the grains of the constituent phases and elements present in the resulting MgB2 sample (including the information of size and shapes of constituent crystallites in case of MgB2 grains).…”
Section: Introductionmentioning
confidence: 99%